Bovine Tuberculosis and Brucellosis in Cattle and African Buffalo in the Limpopo National Park, Mozambique. Issue 6 (31st January 2014) - Tanner, M.; Inlameia, O.; Michel, A.; Maxlhuza, G.; Pondja, A.; Fafetine, J.; Macucule, B.; Zacarias, M.; Manguele, J.; Moiane, I. C.; Marranangumbe, A. S.; Mulandane, F.; et al.
Summary Bovine tuberculosis (BTB) and brucellosis are prevalent in buffaloes of the Kruger National Park (KNP, South Africa). Both diseases were considered to have no or a very low prevalence in wildlife and livestock in and around the Limpopo National Park (LNP, Mozambique). The same applies for tuberculosis in Gonarezhou National Park (GNP, Zimbabwe), but just recently, BTB was detected in buffaloes in the GNP and fears arose that the disease might also spread to the LNP as a result of the partial removal of the fences between the three parks to form the Great Limpopo Transfrontier Park. To assess the status of both diseases in and around LNP, 62 buffaloes were tested for bovine tuberculosis (BTB) and bovine brucellosis. The percentage of positive BTB reactors in buffalo was 8.06% using BovidTB Stat‐Pak® and 0% with BOVIGAM® IFN‐γ test and IDEXX ELISA. The brucellosis seroprevalence in buffalo was found to be 17.72% and 27.42% using Rose Bengal Test (RBT) and ELISA, respectively. In addition, 2445 cattle in and around the LNP were examined for BTB using the single intradermal cervical comparative tuberculin test (SICCT), and an apparent prevalence of 0.98% was found with no significant difference inside (0.5%) and outside (1.3%) the park. This is the first published report on the presence of positive reactors to BTB and bovine brucellosis in buffalo and cattle in and outside the LNP. Monitoring the wildlife–livestock–human interface of zoonotic high‐impact diseases such as BTB and brucellosis is of outmost importance for the successful implementation and management of any transfrontier park that aims to improve the livelihoods of the local communities.